Analysis of image steganography using AES / Nur Amira Muhamad Ghazali - Muhamad Ghazali, Nur Amira (2020)
Data hiding and encapsulation are both important concepts of Data hiding emphasizes so much on data protection and encapsulation emphasizes mostly on covering the complexity of the program. As our privacy is important in this modern world due to data stealing, both methods are widely used. However, the effectiveness of this method does have some lack in terms of security. This project aims to provide better security in data hiding as this project improves the security of existing system from the past research. Based on the past research, it is only providing the encryption and decryption of the text without hiding the text. In this project, we combine the method of cryptography and steganography using Advanced Encryption Standard (AES) and Least Significant Bits (LSB) algorithms. At first, the plaintext was encrypted to cipher text and hidden in the image. There is also decryption so the user can get back to the original data. Finally, as the result of the implementation, the user will receive an image with hidden data. The project is developed using Matlab software.